The role of NLRP3 inflammasome in inflammation-related skeletal muscle atrophy - Liu, Yukun; Wang, Dongfang; Li, Tianyu; Yang, Fan; Li, Zhanfei; Bai, Xiangjun; Wang, Yuchang (Frontiers in Immunology, 2022)
Skeletal muscle atrophy is a common complication in survivors of sepsis, which affects the respiratory and motor functions of patients, thus severely impacting their quality of life and long-term survival. Although several advances have been made in investigations on the pathogenetic mechanism of sepsis-induced skeletal muscle atrophy, the underlying mechanisms remain unclear. Findings from recent studies suggest that the nucleotide-binding and oligomerisation domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, a regulator of inflammation, may be crucial in the development of skeletal muscle atrophy. NLRP3 inhibitors contribute to the inhibition of catabolic processes, skeletal muscle atrophy and cachexia-induced inflammation. Here, we review the mechanisms by which NLRP3 mediates these responses and analyse how NLRP3 affects muscle wasting during inflammation.